Consumption of benzodiazepines without prescription among first-year nursing students at the University of Guayaquil, school of nursing, Ecuador (Revista Latino-Americana de Enfermagem, 2008)
This study aimed to determine the consumption of benzodiazepines without prescription among first-year students from a nursing school of a public University in Ecuador. This is a descriptive, transversal and explanatory study with a quantitative approach. A questionnaire was used for data collection. The population studied was of 181 students. The results showed that 10.5% of the students had consumed benzodiazepine without prescription once in their lives. Of these, 6.1% consumed benzodiazepine in the last year, and 3.9% are currently consuming it. The diazepam was the most consumed BZD without prescription and pharmacies, were the place of higher access. The main reasons for the benzodiazepine consumption were: insomnia, anxiety, stress, depression, family and economical problems. The use of benzodiazepines with non-medicinal purposes is related to problems such as memory loss, retirement syndrome and sedation. When benzodiazepines are consumed jointly with alcohol or other drugs they can lead to coma or death. This study shows the serious consequences benzodiazepines cause when used by nursing students in Ecuador.